Implementasi Metode Problem-Based Learning (PBL) untuk Optimalisasi Student-Centered Learning (SCL) di Perguruan Tinggi - Putu Santi Oktarina (Jurnal Penjaminan Mutu, 2017)
Students at higher education institutions are definitely adults who should be encouraged and given motivation to be the 'adult' learners. Each student has diverse characteristics that will make them ultimately bring different perspectives to the class (different types of backgrounds, learning styles, experiences, and aspirations). Therefore, educators are no longer possible to use conventional methods in cultivating the values to students to get them to be adult learners. The psychological condition of adults will encourage the teaching and learning process to be more directed to the Student-Centered Learning. This method is built on the principles of active learning constructive, some social activity, mental reflection, implementation of prior knowledge, and so forth. The learning process is a reflection cycle (about what happened), the idea of a thing (or something that needs to be tested), action (trial to do something), and outcomes (concrete experience). Problem-Based Learning method is an option that can be used to support the activities of Student-Centered Learning for the use of problems in the learning process can trigger the curiosity of students that will lead them to be able to solve their own problems by giving a definition of a certain problem and specify the collected information. In this way, students will try to associate the information they have and be able to specify the topics they will learn more.